Closed-loop control of extracorporeal oxygen and carbon dioxide gas transfer. (February 2017) - Brendle, C.; Hackmack, K.-F.; Kühn, J.; Wardeh, M.N.; Janisch, T.; Kopp, R.; Rossaint, R.; Stollenwerk, A.; Kowalewski, S.; Leonhardt, S.; Walter, M.; Misgeld, B.
Abstract: Additional extracorporeal gas transfer facilitates ultra-protective mechanical ventilation during treatment of severe lung disease. The proposed automation contributes to both patient safety and therapeutic success. A decentralized control system set the oxygen and carbon dioxide gas transfer rates. The controlled variables are estimated using standard measurement devices without direct blood contact. To reduce patient stress, an outer-loop integral controller adjusts the extracorporeal blood flow. The control system was first evaluated in silico and then in vivo using an animal model. Finally, the method is shown to be feasible and its response time is sufficient to meet patients' clinical needs. Abstract : Highlights: Continuous control of extracorporeal O2 and CO2 gas transfer rates is proposed. Only non-invasive sensors (e.g. in gas phase) are used (no blood gas analysis). A decentralized closed-loop control system with robust controllers is presented. Control system was evaluated in silico and in vivo . Results suggest that application for physiological target control is feasible.